Therapeutic efficacy of topical luliconazole versus topical ketoconazole in the treatment of pityriasis versicolor patients: a hospital based comparative study - Hassan, Shahid; Ranjan, Ashutosh (International Journal of Research in Dermatology, 2020)
Background: To evaluate the clinical efficacy of 1% topical luliconazole versus 2% topical ketoconazole in pityriasis versicolor patients. Methods: Mycological examination of all the pityriasis versicolor patient was done by using skin scrapings were collected from the skin lesions to prepare for 10% KOH mount, which was examined under the microscope to note the findings as KOH mount positive or negative for Malassezia fungi. KOH mount positive or negative was noted at 0 days, 2 weeks and 4 weeks continued treatments with luliconazole and ketoconazole. Results: At the first days, majorities of patients 46 (92%) of luliconazole group were positive for KOH mount. At 14 days treatment with luliconazole, patients had 11 (22%) positive for KOH mount. At the 28 days treatment with luliconazole, only 2 (4%) patients were positive and most of the patients 49 (98%) were negative for KOH mount. Similarly, in ketoconazole group patients, 47 (94%) patients were positive for KOH mount in beginning of treatment. At 14 days treatment with ketoconazole 16 (32%) patients were positive and 34 (68%) patients were negative for KOH mount. And at the 28 days with treatment of ketoconazole 13 (26%) patients were positive and most of the patients 37 (74%) were negative for ketoconazole. Conclusions: Male population as well as age 26-35 years were more prone for pityriasis versicolor infection. On two weeks of treatment luliconazole and ketoconazole had near about similar efficacy against pityriasis versicolor. But, on continue 4 weeks of treatment regimens topical luliconazole had more clinically efficacious than ketoconazole against pityriasis versicolor.